Deep semantics and the evolution of new scientific theories and discoveries - Adi, Tom, 1950- (IGI Global, 2019)
"This book explores and explains how deep semantics works, how new deep semantics research can be conducted, and how the new scientific method of deep semantics can be used to create new scientific theories and discoveries"--